EDUCATIONAL FUNCTIONS OF YOUTH MUSIC SUBCULTURES IN THE FORMATION OF SPIRITUALITY SENIOR STUDENT - N.V. Dolgaya (Academy of Cognitive and Natural Sciences, 2002)
The definite explanation of the conception of subculture has been exposed, and the causes of its origin, its components, and its specific peculiarities have been considered. The educational functions of musical subculture of youth for forming of senior pupil's spirifmillts have been done.